2021
DOI: 10.1182/blood-2021-153277
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Outcomes and Predictors of Response in Patients with Relapsed Mantle Cell Lymphoma Treated with Brexucabtagene Autoleucel

Abstract: Background: Brexucabtagene autoleucel (brexu-cel) is the first CD19 chimeric antigen receptor T-cell (CAR T) therapy approved for use in patients (pts) with relapsed mantle cell lymphoma (MCL). The ZUMA-2 trial demonstrated that brexu-cel induces durable remissions in these pts with an ORR of 85% (59% CR), estimated 12-month PFS rate of 61%, and similar toxicity profile to other CAR T therapies (Wang et al, NEJM 2020). We conducted a multicenter, retrospective study of pts treated with commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
2
11
0
4
Order By: Relevance
“…Neurological complications appeared in the same percentage, 58%, of patients as in the ZUMA-2 study, also a grade 3 NAs (33%). The authors confirmed encouraging results in activity and safety of brexu-cel in relapsed and refractory disease in real world practice, especially as 75% of patients would never receive CAR-T as participants in the ZUMA-2 study [54].…”
Section: Car-t Products In MCLsupporting
confidence: 55%
See 3 more Smart Citations
“…Neurological complications appeared in the same percentage, 58%, of patients as in the ZUMA-2 study, also a grade 3 NAs (33%). The authors confirmed encouraging results in activity and safety of brexu-cel in relapsed and refractory disease in real world practice, especially as 75% of patients would never receive CAR-T as participants in the ZUMA-2 study [54].…”
Section: Car-t Products In MCLsupporting
confidence: 55%
“…Two patients died due to progressive disease. No adverse factors were found for survival in univariate analysis [54].…”
Section: Car-t Products In MCLmentioning
confidence: 80%
See 2 more Smart Citations
“…In ZUMA-2, CRS and neurotoxicity were managed with tocilizumab or glucocorticoids; however, some cases required vasopressor therapy [ 12 ••]. In real-world studies of brexu-cel, incidences of CRS and neurotoxicity were generally similar to those observed in the ZUMA-2 trial (Table 1 ) [ 50 ••, 54 , 56 ] and were primarily managed with tocilizumab and corticosteroids [ 50 ••, 55 ]; ICU admission was required in 21–28% of patients [ 50 ••, 56 ]. Recent evidence suggests that early administration of the interleukin 1 receptor antagonist anakinra may reduce the occurrence and severity of CRS and neurotoxicity in patients receiving CAR T-cell therapy [ 65 – 67 ].…”
Section: Btk Inhibitors For R/r MCLmentioning
confidence: 96%